DESIGN AND EVALUATION OF FORSKOLIN BUCCAL MUCOADHESIVE MICROSPHERES - T., Saritha; Balaji, Anna; A., Jaswanth (International Journal of Current Pharmaceutical Research, 2015)
Objective: The objective of the present study was to develop buccal mucoadhesive microspheres of Forskolin (FSK) for hypertension. Methods: The microspheres were prepared by orifice ionic gelation method using different ratios of Sodium alginate and Kondagogu gum. Fourier-transformed infrared (FTIR) spectroscopy study shows that drug and other excipients are compatible with each other. A 22 full factorial design was applied to optimize the formulation considering concentration of Sodium alginate and Kondagogu gum as independent variables; % swelling index and In vitro % muco adhesion as dependent variables. Results: The prepared formulations were characterized for % yield, drug entrapment efficiency, scanning electron microscopy (SEM) and in vitro drug release. Microspheres prepared with the ratio of sodium alginate: kondagogu gum (1:1.5) showed swelling index 37±3 % and in vitro mucoadhesion 73±3%. SEM images confirmed that microspheres are a hollow spherical structure to a smooth surface morphology. The drug entrapment efficacy of all the formulations was in the range of 58.42±1.2–79.52±1.5 %. Conclusion: The values of coefficient correlation (r) were calculated and were found to be zero order release from prepared formulation (K2).